Analisis Sidik Lintas Beberapa Karakter Komponen Hasil Terhadap Daya Hasil Padi Sawah Pada Aplikasi Agrisimba - ROHAENI, WAGE R.; PERMADI, KARSIDI (Agrotrop : Journal on Agriculture Science; Vol 2 No 2 (2012), 2014)
Pathway analysis is the further test after correlation test. Correlation between characters of plant will be change in one field condition to other condition field. Correlation between characters on organic or semi-organic farming system still studied limitedly included in our project about organic/semi-organic farming. Agrisimba is the probiotic microbes, one of technology for decomposing straw rapidly. The study was done on November 2011 – March 2012 in Sawah Kidul Village, Pasawahan – Purwakarta District with “farmer participatory on farm research method”. Inpari 13 was the indicator variety and Agrisimba was the treatment to decomposing straw rapidly in rice field to support organic farming system as this topic study. Correlation analysis showed that plant high and value of pithy grain/tassel have level of closeness significantly with yield character. On further test analysis showed that plant high was the highest value of direct influence and 100 grain weight was highest value of indirect influence for yield character.
Keywords: Agrisimba, correlation, direct and indirect influence, rice, yield